1999
DOI: 10.1083/jcb.144.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Association of BiP with Newly Synthesized Proteins Is Dependent on the Rate and Stability of Folding and Not Simply on the Presence of Sequences That Can Bind to BiP

Abstract: Immunoglobulin heavy chain-binding protein (BiP) is a member of the hsp70 family of chaperones and one of the most abundant proteins in the ER lumen. It is known to interact transiently with many nascent proteins as they enter the ER and more stably with protein subunits produced in stoichiometric excess or with mutant proteins. However, there also exists a large number of secretory pathway proteins that do not apparently interact with BiP. To begin to understand what controls the likelihood that a nascent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Thus, these results provide no evidence for the creation of a better BiP site, but rather predict reduced or no change in BiP binding to this putative site. Although the predicted BiP score does not suggest increased BiP binding, this result should be interpreted with caution given that Hellman et al (42) demonstrated that there was no correlation between the presence of predicted BiP binding sequences and actual BiP binding to murine I variable and constant domains. Further analysis is required to determine whether Ile 51 is part of a BiP-binding site used in vivo and whether the single mutations affect this interaction.…”
Section: Mechanism Of the Secretion Defectmentioning
confidence: 60%
“…Thus, these results provide no evidence for the creation of a better BiP site, but rather predict reduced or no change in BiP binding to this putative site. Although the predicted BiP score does not suggest increased BiP binding, this result should be interpreted with caution given that Hellman et al (42) demonstrated that there was no correlation between the presence of predicted BiP binding sequences and actual BiP binding to murine I variable and constant domains. Further analysis is required to determine whether Ile 51 is part of a BiP-binding site used in vivo and whether the single mutations affect this interaction.…”
Section: Mechanism Of the Secretion Defectmentioning
confidence: 60%
“…Lau et al hsp70 family of chaperones, is one of the most abundant proteins in the ER lumen. BiP has been implicated in cotranslational folding of nascent polypeptides and in the recognition and disposal of aberrant polypeptides (Hatano et al, 1997;Hellman et al, 1999). Interestingly, calnexin and calreticulin, two closely related molecular chaperones in rough ER, when associated with BiP, suppress aggregation and promote refolding of protein and glycoprotein substrates (Stronge et al, 2001).…”
Section: Post Hoc Semiquantitative Rt-pcr Analyses Of Trpm2 (A) Ribomentioning
confidence: 99%
“…15 In vivo, the accessibility of a binding site may be determined by the folding kinetics of the respective domain as it had been shown that stronger BiP interactions are observed if the folding of a protein is decelerated in vivo. 16,17 Like other Hsp70 chaperones, BiP assists folding of the substrate by repeated cycles of binding and release, driven by ATP-dependent conformational changes of the chaperone. 18 The regulation of this ATPase cycle is best understood for the E. coli Hsp70 homologue DnaK.…”
Section: Introductionmentioning
confidence: 99%